Crise do modelo do jornalismo comercial e emergência do jornalismo cidadão - Folter, Regiane Martins [UNESP] (2014)
Corporative media, represented by TV, radio, press and internet conglomerates, is responsible for the biggest portion of audience and public all over the world. The commercial media was built upon media concentration and monopoly strategies and this business aims society’s economic and political control. Unfortunately, they don’t represent the biggest portion of population’s interests and, because of that, corporative media faces a crisis moment while alternative means of communication rise from the initiative of professionals who are committed to society’s marginalized sectors. Radical media intends to express a variant vision about hegemonic policies, priorities and perspectives. Citizen journalism is one of radical media arms and this research proposition is to analyze the business model of commercial media in Brazil and in the world, its means of production, and compare them with citizen journalism methods. This work also intends to analyze radical media and how it is opposite to corporative media by studying Escola de Notícias, an educommunication project from São Paulo